Editorial Peer Review: Its Strength and Weaknesses. - David Flaxbart (Issues in Science and Technology Librarianship)
This article reviews the book Editorial Peer Review: Its Strength and Weaknesses. (ASIST monograph series) Medford NJ: American Society for Information Science and Technology, 2001 by Ann C. Weller.